Adversity's Impact on Adults' Self-Report and Physiological Difficulties with Emotion Regulation: Appraisal as a Moderating Mechanism. Issue 4 (3rd April 2023) - Gusler, Stephanie; Jackson, Yo
ABSTRACT: Globally, there is a high prevalence of adversity exposure, and there is evidence indicating a linear association between adversity exposure, particularly childhood adversity, and adults' psychological distress. To better understand this association, researchers have examined the role of emotion regulation abilities, which are thought to impact and underlie one's psychological well-being. The present study examined the association between childhood versus adulthood adversity exposure and self-reported difficulties with emotion regulation and physiological indicators of emotion regulation (e.g., resting respiratory sinus arrythmia [RSA], RSA reactivity, and RSA recovery). Further, the study assessed appraisal styles (i.e., patterns of subjective interpretations) across adverse life events as a possible moderator to help explain why some, but not all, exposed to adversity may display emotion regulation difficulties. Participants were 161 adults participating in a larger federally funded project. Results found no direct association between childhood or adulthood adversity exposure and self-reported or physiological indicators of difficulties with emotion regulation. However, adulthood adversity exposure was associated with stronger trauma appraisal styles, and stronger trauma appraisal styles were associated with greater self-reported difficulties with emotion regulation and greater RSA reactivity. Results also showed interactions between greater childhood adversity and stronger trauma appraisal styles for lower resting RSA and greater RSA recovery. The present study demonstrates that emotion regulation is complex, dynamic, and has multiple dimensions and that childhood adversity may impact internal regulatory processes, but only in conjunction with trauma appraisal styles, which are associated with adulthood adversity.